A gestão educacional no Município de Araraquara: a questão dos Conselhos. - Ramacciotti, Juliana Aparecida Marinho Aldred (Universidade Federal de São Carlos, 2006)
This work introduces a study of the implementation and running of the councils of popular participation related to the educational area in the Municipal Corporation of Araraquara. Since the possession of the affiliation designated as Democratic and Popular Front, in 2001, guided by the Workers Party (PT), and still formed by the Brazilian Socialist Party (PSB) and the Communist Party of Brazil (PC do B), the policy adopted is the decentralization one, assumed as being the best way for democratization in the public power scope. Since the beginning in 2001, the administration of the Democratic and Popular Front showed preoccupation in amplifying the spaces for popular participation. With the motto The Society Generating Public Policies , it instituted several Municipal Councils and restructured those who already existed. There are in this Municipal Corporation three councils directly related to education that were analyzed: the Municipal Council of Education, the Council of School Nourishment and the Municipal Council of Attendance and Social Control of the Maintenance and Development Fund of Elementary School and Valorization of Teacher Education (FUNDEF). Through the analysis of documents and observations in some meetings, the work searched for identifying elements for a discussion on the real representativeness that the society has in those councils, in the light of Norberto Nobio s theory on the development of the democracy in the complex current society. The promises non accomplished by the modern democracy, according to Bobbio, added to the essential stages of acting of the council, pursuant Perseu Abramo, were used as a basis for the proposed analysis. Initially, the text shows, briefly, from the historical passage of the Brazilian Politics, from the 60 s to 1988 (Enactment of the Federal Constitution), focusing on the issue of the education democratization in a national scope, after in the State of Sao Paulo and finally in the Municipal Corporation of Araraquara. Then, basing on the data from direct observation and documents, the text tries to demonstrate how the analyzed councils are introduced, their composition, attribution and the possibility of contributing to the democratization of the public administration and to the improvement of governmental policies.
Keywords: Educação - consciência crítica; Gestão participativa; Democratização da educação; Gestão educacional; Education democratization; Participative councils; Educational administration; CIENCIAS HUMANAS::EDUCACAO